Fuel characterization and crown fuel load prediction in non-treated Calabrian pine (Pinus brutia Ten.) plantation areas - Yurtgan M; Baysal I; Küçük O (Italian Society of Sivilculture and Forest Ecology (SISEF), 2022)
Successful management of young, fire-prone Calabrian pine forests requires an accurate characterization of surface and canopy fuel loads at stand level. This study characterizes the surface and canopy fuel characteristics in unthinned Calabrian pine plantations in Turkey. Fifteen sample plots were measured to determine the surface and crown fuel characteristics of very young, young and middle aged Calabrian pine stands (10 to 28 years old). Thirty-six trees were destructively sampled to quantify the crown fuel loads and canopy fuel characteristics of the stands. Surface fuel load ranged from 11.38 t ha-1 in the young stands to 35.27 t ha-1 in the middle aged stands. Dead fuel load as ladder fuels on the trees ranged from 0.77 kg in very young stands to 13.56 kg in the young stands. Live fuel loads on the trees ranged from 0.77 kg to 23.29 kg in the young aged stands. Total active crown fuel load was 58.7%, 52.1% and 49.5% of total crown fuel load in very young, young and middle aged stands, respectively. Our results improve the current crown fuel model predictions and showed the importance of dead fuel load in fire management studies both for the determination of crown fuel loads and the calculation of carbon stocks.
Keywords: Surface Fuel; Türkiye; Non-treated; Pinus brutia; Forestry; Live Crown Fuel; SD1-669.5; Dead Crown Fuel; 15. Life on land